An Analysis Of The Community Satisfaction Index (IKM) Toward Public Service Delivery At The Department Of Population And Civil Registration Lebong Regency - Dian, Dian; Soleh, Ahmad; Made E.G, Ida Ayu (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to determine the Community Satisfaction Index (IKM) regarding public services at the Department of Population and Civil Registration of Lebong Regency. This research employs a quantitative approach referring to nine elements of public service, namely: service requirements; system, mechanism, and procedure; completion time; cost/tariff; service products according to specifications; implementer competence; implementer behavior; facilities and infrastructure; as well as handling of complaints, suggestions, and feedback. The results of the study indicate that, overall, the quality of services at the Department of Population and Civil Registration of Lebong Regency falls into the very good category, with a Community Satisfaction Index score of 3.78 and a converted index quality score of 94.63. These findings show that the public is satisfied with the services provided, and that public service implementation has been effective and in accordance with established standards.